Overhauser‐enhanced magnetic resonance elastography. (24th February 2016) - Salameh, Najat; Sarracanie, Mathieu; Armstrong, Brandon D.; Rosen, Matthew S.; Comment, Arnaud
Abstract : Magnetic resonance elastography (MRE) is a powerful technique to assess the mechanical properties of living tissue. However, it suffers from reduced sensitivity in regions with short T 2 and T 2 * such as in tissue with high concentrations of paramagnetic iron, or in regions surrounding implanted devices. In this work, we exploit the longer T 2 * attainable at ultra‐low magnetic fields in combination with Overhauser dynamic nuclear polarization (DNP) to enable rapid MRE at 0.0065 T. A 3D balanced steady‐state free precession based MRE sequence with undersampling and fractional encoding was implemented on a 0.0065 T MRI scanner. A custom‐built RF coil for DNP and a programmable vibration system for elastography were developed. Displacement fields and stiffness maps were reconstructed from data recorded in a polyvinyl alcohol gel phantom loaded with stable nitroxide radicals. A DNP enhancement of 25 was achieved during the MRE sequence, allowing the acquisition of 3D Overhauser‐enhanced MRE (OMRE) images with (1.5 × 2.7 × 9) mm 3 resolution over eight temporal steps and 11 slices in 6 minutes. In conclusion, OMRE at ultra‐low magnetic field can be used to detect mechanical waves over short acquisition times. This new modality shows promise to broaden the scope of conventional MRE applications, and may extend the utility of low‐cost, portable MRI systems to detect elasticity changes in patients with implanted devices or iron overload. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : MR elastography (MRE) is a powerful technique to assess the mechanical properties of living tissue. Here, we exploit the longer T2 * attainable at ultra‐low magnetic fields in combination with Overhauser dynamic nuclear polarization to enable rapid MRE. At 0.0065 T, Overhauser‐enhanced MRE with 8 temporal steps was performed in 6 minutes, providing opportunity for magnetic susceptibility artifact‐free MRE. Low‐field MRE could provide a simple and portable system for detection of elasticity changes in subjects with iron overload or implanted devices.